AB1423-HPR Impact of osteoarthritis on work participation: a systematic review. (12th June 2018) - Secchi, S; Holder, C.; Prior, Y.
Abstract : Background: Osteoarthritis (OA) is a common musculoskeletal condition in working age adults and linked to substantial reduction is work productivity and increased risk of work loss. 1, 2 Objectives: This systematic review aimed to investigate the impact of OA on the individual's work participation to identify targets for interventions and reduce the risk of future work loss. Methods: Database searches included the Cochrane Library, Medical Literature Analysis and Retrieval System Online, Excerpta Medica Database, Cumulative Index to Nursing and Allied Health literature, King's Fund, Allied and Alternative Medicine, Psychological Information Database, Applied Social Sciences Index and Abstracts, Ageline, Social Services Abstracts and British Nursing Index from earliest to November 2017. The PRISMA statement was used to guide the process. Observational, interventional and qualitative studies were included in the review and their methodological quality was assessed by two researchers using the Johanna Brigg Institute Checklists. Results: Twenty-two studies, which were published in 2007 to 2016 (12 cross sectional; 5 cohort; and 5 qualitative) were included. Measurement of workplace limitation varied largely amongst the studies. High pain intensity, decreased physical functioning, physically demanding jobs, lack of opportunities to re-train, and lack of co-worker support were identified as important workplace factors associated with loss of productivity, and both presenteeism and absenteeism were predictive of job disruption and premature work loss. Function was identified as an important mediator of the impact of pain on work productivity, with physiotherapy and exercise classes that target pain and physical function 3 and maximising work place support 4 being recommended to prevent or reduce loss of work productivity. Qualitative studies emphasised the significance of physical environments, and social networks and support, recommending interventions to target individual needs to prevent future work loss. 5 Conclusions: There is a wide range of scientific literature to suggest working people with OA are experiencing work instability due to pain, reduced physical functioning, activity limitation, and lack of co-worker and workplace support, placing them at increased risk of work disability. However, the measurement of workplace limitation varies greatly in this literature, making it hard to conduct empirical comparisons. Due to the temporal and biopsychosocial nature of work disability, there is a need for longitudinal studies to investigate the links between workplace factors and the onset and persistence of work instability in people with OA. Additionally, future qualitative studies should explore the role of personal and psychological factors, such as an individual's self-efficacy and coping skills, and the employer's perspectives on the provision of workplace support, to establish whether these potentially modifiable factors could influence work outcomes in people with OA. References: [1] Kingsbury, et al. Rheumatology2014;53:937–947 [2] Sharif, et al. Rheumatology2016;55:861–868 [3] Wlikie, et al. PlosOne2015;10(4):e0120042. [4] Wilkie, et al. Rhuematology2014;53:459–469 [5] Bromann, et al. Dis & Rehab2014;36:19 Acknowledgements: This project was funded by the National Centre of Excellence for Musculoskeletal Health and Work (CMHW); a multidisciplinary collaboration funded by Arthritis Research UK and the Medical Research Council (MRC). Disclosure of Interest: None declared